Nurse safety in pre-hospital care for patients with suspected or confirmed COVID-19: An integrative review (Research, Society and Development, 2021)
The study aims to promote the continuing education of professionals working in the Pre-Hospital Care of suspected or confirmed cases of COVID-19, reinforcing the necessary care in this context. This is an integrative review, whose data collection took place in the Virtual Health Library (VHL), where data from LILACS, SciELO, Bdenf, Medline, among others, are available. Six publications were selected from 2019 to 2021. After analyzing the data collected, applying the inclusion and exclusion criteria, the following categories emerged: Health professional safety and Patient safety. It was observed that knowledge and qualified assistance maximize the possible results for the patient and ensure the professional's safety throughout the patient care process. In addition, the correct application of protection measures reflects in the containment of the coronavirus propagation.